Conceptualising toleration. Issue 2 (23rd February 2020) - Horton, John
ABSTRACT: This discussion focuses primarily on conceptual issues and on three specific features of Peter Balint's argument in particular. First, I seek to assess his boldest conceptual innovation, the abandonment of what is known as 'the objection component' as an essential component of toleration within his broader understanding of the concept. Instead, I suggest an intermediate position between the 'orthodox' conception and his view. Secondly, I raise some mildly sceptical questions about how far we can make sense of a purely 'descriptive' sense of toleration. Finally, I offer a modest clarification of the conceptual dimension of the argument that Balint advances against those who deny that the liberal state can be both neutral and tolerant, showing that the disagreement is less fundamental than it may initially appear.